(untitled) (Comprehensive Journal of Science, 2025)
Due to the increasing demand for photovoltaic energy as a key component in the transition toward sustainable energy in many countries around the world—where agricultural land is used sustainably to preserve natural landscapes and human well-being—new models, approaches, and market sectors have emerged that take into account integrated systems. Among these integrated systems, agrivoltaics has appeared as a highly promising option to achieve mutual benefits within the food–energy–water nexus. Experimental projects have been developed worldwide, resulting in the exchange of information and experiences among these countries to reach diverse and suitable solutions, which are then designed to achieve commercial-scale applications based on considerations of water and energy use efficiency as well as agricultural productivity, while taking into account the associated environmental impacts that influence the selection of specific and appropriate designs to preserve agricultural and natural ecosystems. Therefore, this study reviews the available technological and spatial design options that enable the identification of the key features of the system from a multidisciplinary perspective